Research on the Reconstruction Strategy of Rock Music Lyrics from the Perspective of Mediatization (Journal of science and technology exploration, 2026)
In the era where media platforms deeply participate in content production, the textual presentation logic of Chinese music variety shows has undergone significant changes. After rock works enter mainstream variety shows, they often undergo systematic lyric adjustments. This paper uses the mediaization theory as the analytical framework, based on the "original lyrics - broadcast lyrics" sentence-by-sentence comparison of more than thirty works in programs such as "Summer Band", and adopts descriptive content analysis and text comparison analysis to summarize the structural characteristics and operational paths of lyric rewriting in the program context. The research finds that under the joint influence of platform rules, broadcasting norms, and narrative rhythm, the program production tends to achieve "broadcastable expression" through language neutrality, semantic intensity adjustment, and image generalization; as a result, expressions in the original work that are highly directional, have high emotional intensity, or have a high risk of cross-cultural understanding are weakened or restructured, but social experience and young emotions do not disappear; instead, they are retained in metaphorical, emotional, and positive ways. This paper can provide references for rock lyric creation, variety show text construction, and understanding of youth culture.
Keywords: Mediaization; Rock music; Lyric rewriting; Variety show; Cultural construction